The changes of opium and opium derivates that were analysed at the council of forensic medicine between 1990 and 2000 - Toprak, Sadık; Özağ, M. Kadir; Aksu, Murat; Yıldırım, Ali; Çetin, İlhan (Journal of Dependence, 2008)
Objective: Opium abuse has a long history in the World and Anatolia. The opium policy of Turkey has been changed considerably after 1930’s and opium production limited to medical reasons since 1970’s. The aim of the study was to demonstrate the changes of seized opium and derivates between 1990 and 2000. Method: All reports about drugs (2862) that were performed at the Council of Forensic Medicine, Ministry of Justice in Istanbul, between 1990-2000 were reviewed. Opium and derivates were included into the study. Results: At the period of 11 years that the study covered, there were 1435 heroin seizures in total. In general, there was an increasing trend. At the same period, there were 724 morphine seizures. Apart from a peak occurred in 1994 and 1996, the trend was stable. Lastly, there were 109 opium seizures. Mean morphine weight was found 2.5 kg. Conclusion: At the period of 1990 and 2000, number of heroin seizures and mean weight were increasing. On the other hand, number of morphine seizures and mean weight were relatively stable. In this case, it can be argued that Turkey was becoming a transit country in the drug trade rather than a productive country.